FEEDING AND REPRODUCTION OF AQUARIUM FISH (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The care and breeding of aquarium fish require a deep understanding of their feeding habits, dietary needs, and reproductive behaviors. Each species has specific requirements for optimal health, growth, and successful reproduction. This article delves into the key aspects of feeding aquarium fish, from types of diets to feeding frequencies, and explores various methods for fostering successful reproduction, including tank preparation, water quality, and managing offspring. By understanding these factors, aquarium enthusiasts can create a healthy environment that supports the well-being and longevity of their fish.